Troy Bickham, Eating the Empire. Food and Society in Eighteenth-century Britain - Jaine, Tom (Petits Propos Culinaires, 2020)
Troy Bickham, Eating the Empire. Food and Society in Eighteenth-century Britain. Reaktion Books, 2020; 285 pp., hardback, 89 illustrations, £20.00.